Pengaruh Komisaris Independen, Intensitas Modal dan Sales Growth terhadap Agresivitas Pajak: Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2018-2022 - Apriyadi, Reza; Syahputra, Andri (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study was conducted to determine the effect of independent commissioners, capital intensity, and sales growth on tax aggressiveness (Empirical study of mining companies listed on the IDX in 2018-2022). This study uses quantitative research methods with secondary data. The purposive sampling method was used for the data collection method and the sample obtained was 19 companies. Data analysis uses panel data regression techniques with random effect models to test the hypothesis. Hypothesis testing in this study using multiple linear regression using Eviews version 12. The results of this study indicate that simultaneously showing independent commissioners, capital intensity and sales growth together have an effect on tax aggressiveness. The independent variable in the dependent variable is 12.43% while the remaining 87.57% is explained by other variables besides the variables used in this study. The results of this study indicate that partially independent commissioners have no effect on tax aggressiveness, capital intensity affects tax aggressiveness and sales growth affects tax aggressiveness.